2016
DOI: 10.1080/26390043.2016.12067805
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Service Teacher Attitudes Toward English Language Learners

Abstract: Enrollment of English language learners (ELLs) in United States schools has increased more rapidly than general enrollment, resulting in an urgent need for teachers to be prepared and to meet the needs of ELLs in their classrooms. This study examined the language learning beliefs and attitudes toward ELLs among 286 pre-service teachers in a large public university. Results show that pre-service teachers demonstrated neutral attitudes toward ELLs. Participants' language learning beliefs exhibited four component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Another significant point regarding the results is that despite being common among students and teachers alike that American English seems a more acceptable variety of the English language, the statement related to this did not record a high mean score in the present study (M=3.77), which is the borderline between negative and neutral. The results match those of Dixon et al (2016) who found that their participants held neutral to slightly positive attitudes towards the English language. However, Berowa et al's (2018) results are in stark contrast with the present study's results that revealed Vietnamese students positively perceived the English language which is, in turn, consistent with Orfan's (2020) study investigating Afghan undergraduate students' attitudes towards the English language and that demonstrated that students had positive attitudes in all the three components of attitude.…”
Section: Kurdish Students' Attitudes Towards the English Languagesupporting
confidence: 84%
“…Another significant point regarding the results is that despite being common among students and teachers alike that American English seems a more acceptable variety of the English language, the statement related to this did not record a high mean score in the present study (M=3.77), which is the borderline between negative and neutral. The results match those of Dixon et al (2016) who found that their participants held neutral to slightly positive attitudes towards the English language. However, Berowa et al's (2018) results are in stark contrast with the present study's results that revealed Vietnamese students positively perceived the English language which is, in turn, consistent with Orfan's (2020) study investigating Afghan undergraduate students' attitudes towards the English language and that demonstrated that students had positive attitudes in all the three components of attitude.…”
Section: Kurdish Students' Attitudes Towards the English Languagesupporting
confidence: 84%
“…Teachers' attitudes matter (Dixon, Liew, Daraghmeh, & Smith, 2016). Their attitudes toward their profession as teacher affect students' aspires of involvement in the teaching process (Maryrose & Kingsley, 2018).…”
Section: Teachers' Attitudes Toward Teachingsmentioning
confidence: 99%
“…As Byrnes & Kiger (1994) proposed three factors that comprise English teachers' attitudes in their classrooms, i.e. language politics, ELL intolerance, and language support (Dixon et al, 2016). Further, they gave the examples which make up the language politics factor such as common societal attitudes about the language that claim, for instances, 'English should be the only one language used by the authorities', and 'every migrant has to use English to be admitted as American'.…”
Section: Teachers' Attitudes Toward Teachingsmentioning
confidence: 99%